The Sources and Consequences of Embeddedness for the Economic Performance of Organizations: The Network Effect - Uzzi, Brian (Journal of Economic Sociology, 2010)
In this paper I try to take the term of embededness out of the framework of the common program assumption and to disclose how the embededness and network structure influence economic action. Basing on the existed theory and ethnographic analysis of the 23 clothes production companies I worked out the methodological scheme which depicts the details, functions and the sources of embededness. On the basis of this scheme I formulated and tested a list of hypotheses with the help of the data on network interactions of all the companies producing qualitative female clothes in the New-York sewing industry. It was found out that the embededness is the exchange system providing unique opportunities in comparison to the market and that firms organized as networks had better chances to survive than those who support casual market ties. However there is a pick of positive effect of embededness at a particular level after which it starts going down.